Cerpen Narasi Rindu karya Tommy Duang dan Cerpen Viral karya Mario D. E. Kali dalam Antologi Cerpen Pesan Perdamaian dari Bumi Flobamora (Kajian Psikoanalisa Sigmund Freud) - adol, angelina jumatry; Nai, Firmina Angela; Nurhuda, Aris (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2025)
This research is entitled, “The Inner Conflict of the Main Character of Short Story Narasi Rindu by Tommy Duang and Viral Short Story by Mario D. E. Kali in the Anthology of Peace Messages from Bumi Flobamora”. The focus of this research is how the inner conflict of the main character in the short story Narasi Rindu by Tommy Duang and the main character of the short story Viral by Mario D. E. Kali. The purpose of this study is to describe the inner conflict of the main character in the short story Narasi Rindu by Tommy Duang and the main character in the short story Viral by Mario D. E. Kali by using Sigmund Freud's Psychoanalysis approach Sigmund Freud describes the human mental process called personality which is classified into id, ego, and superego. This research uses data sourced from the short story anthology Messages of Peace from Flobamora Earth, namely data in the form of words, phrases, sentences, and paragraphs. The method used in this research is descriptive qualitative. The results and discussion in this study found that the main character of the short story Narasi Rindu by Tommy Duang has six inner conflicts, namely: past trauma, guilt, economic crisis, deep pain and suffering, worry, and indecision. Meanwhile, the main character of the short story Viral by Mario D. E. Kali found six data on inner conflicts, namely: the struggle between acceptance of death and the desire to survive, the struggle between pain and disappointment, deep feelings of guilt, the struggle between hope and resignation, and past trauma. The inner conflicts in both short stories are influenced by Sigmund Freud's personality system, namely id, ego, and superego, which are solely present in the main characters in the short stories. This personality system shows how the main character's inner conflict is managed.